(untitled) - Marleide da Mota Gomes; Eliasz Engelhardt; Leila Chimelli (Arquivos de Neuro-Psiquiatria)
The intersection between infectious diseases, poverty and mental disease was an important subject to the Brazilian Neuropsychiatry in the early 19th century. José Martins da Cruz Jobim (1802–1878) was engaged in a hygienist approach based on symptomatological and anatomopathological studies. He wrote “Insânia loquaz” (Loquacious insanity), 1831, the first written text about mental illness in Brazil, founded on clinical and pathological data, compatible with tuberculous meningitis. Thus, Jobim deserves the title of the first neuropsychiatrist in Brazil. The authors critically studied the clinical history and the autopsy findings of his cases, and the main health policies at the time.